Toward 6G: An Overview of the Next Generation of Intelligent Network Connectivity - Sivarama Prasad Tera; Ravikumar Chinthaginjala; Giovanni Pau; Tae Hoon Kim (IEEE Access)
The development of 6G networks represents a groundbreaking leap in mobile communication, targeting the creation of an Intelligent Network of Everything that seamlessly integrates advanced technologies such as Artificial Intelligence (AI), Machine Learning (ML), and the Internet of Everything (IoE). This next-generation network is projected to begin standardization in 2025, with commercial deployment anticipated by 2030. Building on the foundation of its predecessors, 6G aims to deliver ultra-reliable, low-latency, and high-speed communication essential for applications like autonomous systems, immersive virtual environments, and smart cities. This article provides a comprehensive overview of 6G, articulating its vision and identifying the core technologies that will enable its transformative capabilities. The key contributions of this work include a detailed exploration of prospective 6G applications and use cases, such as autonomous systems and integrated communication-sensing scenarios. Additionally, it identifies major challenges—such as advanced coding schemes, energy management, and security—and presents a roadmap for future research in these critical areas. The study also reviews potential coding and modulation techniques, such as non-binary codes and lattice codes, assessing their suitability for 6G’s stringent performance requirements. Security and privacy considerations are also covered, proposing a robust architecture across all network layers to address emerging threats. Furthermore, the article compiles a literature review on 6G visions and surveys, providing valuable insights into the current state of research, highlighting gaps, and guiding future studies. Through the exploration of spectrum advancements, antenna technologies, network intelligence, and AI/ML integration, this work establishes a clear vision for how 6G can reshape global communication infrastructure and drive innovation in a hyper-connected world.